Pembelajaran Berkarakteristik Inovatif Abad 21 Pada Materi K3LH dengan Model Pembelajaran Ceramah di Sekolah SMK Negeri 1 Dukuhturi - Sigit , Nugroho (Cakrawala: Jurnal Pendidikan, 2022)
The use of clear strategies in learning can provide direction as the learning process progresses so that the learning objectives that have been set can be achieved optimally and also the learning process can take place effectively and efficiently. Learning strategies are not only useful for teachers but also for students. For teachers, learning strategies can be used as guidelines and references to systematic action in the implementation of learning. For students, the use of learning strategies can facilitate the learning process in learning content, because each learning strategy is designed to facilitate the learning process. In improving students' learning outcomes and learning experiences, teachers need to develop learning strategies tailored to the student's materials and conditions.